Building Students’ Personality for Employment Readiness through Soft-skills Training - Saranya C Saranya C; Rajakumar Guduru (Randwick International of Social Science Journal, 2022)
A winning personality is the physical attribute of a person and is considered as his or her success in personal, academic, and professional careers. However, in the ESL context, most engineering students seem to be unaware of the need for and importance of an appealing personality for achieving success in both personal and professional careers. Although students are given a short-term training in soft-skills by their respective college or institute, engineering students seem to lack aspects of a pleasing personality which helps them in job placements and later in the work environment. Therefore, the main aim of this study is to understand and build engineering students’ personality traits such as enthusiasm, dependability, and teamwork for a successful career. For this purpose, to understand the students’ personality types, 25 engineering students were administered a pre-test based on Carl Jung and Isabel Briggs Myers’ typological approach to personality. Students were helped in building personality through the soft-skills training. The data was analyzed and interpreted both qualitatively and quantitatively. The results indicated that having a pleasing personality and exhibiting soft-skills enables in building students’ individual personality for employment readiness. Implications were offered to students, placement trainers, and teachers. It is concluded that having a charming personality will support students in landing their desired jobs.